2012
DOI: 10.1074/jbc.m111.335273
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptors CB1 and CB2 Form Functional Heteromers in Brain

Abstract: Background: Although CB 1 , the most abundant neuronal receptors, and CB 2 receptors are co-expressed in neurons, the CB 1 -CB 2 relationship is unknown. Results: CB 1 and CB 2 receptors form heteromers in neuronal cells and in the brain. Conclusion: Activation of either receptor leads to negative modulation of the partner receptor via heteromers. Significance: These heteromers may explain previous conflicting results and serve as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
147
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 90 publications
2
147
0
3
Order By: Relevance
“…More recently, coimmunoprecipitation assays in HEK293 cells have suggested that CB 1 R can form heteromers with GPR55 (32). In contrast to CB 1 R, very little is known about the possible existence and functional relevance of heteromers involving CB 2 R. A recent study has shown that CB 2 R heteromerizes with CB 1 R in neuronal cells in culture and in vivo (19). In these systems, coactivation of both receptors results in a negative cross-talk and a bidirectional cross-antagonism (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, coimmunoprecipitation assays in HEK293 cells have suggested that CB 1 R can form heteromers with GPR55 (32). In contrast to CB 1 R, very little is known about the possible existence and functional relevance of heteromers involving CB 2 R. A recent study has shown that CB 2 R heteromerizes with CB 1 R in neuronal cells in culture and in vivo (19). In these systems, coactivation of both receptors results in a negative cross-talk and a bidirectional cross-antagonism (19).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to CB 1 R, very little is known about the possible existence and functional relevance of heteromers involving CB 2 R. A recent study has shown that CB 2 R heteromerizes with CB 1 R in neuronal cells in culture and in vivo (19). In these systems, coactivation of both receptors results in a negative cross-talk and a bidirectional cross-antagonism (19). However, CB 2 R signaling can be conceivably more relevant in non-differentiated cells, in which the receptor is highly abundant, than in terminally differentiated cells such as neurons, in which the receptor is scarce (3,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is controversy regarding the effects of endocannabinoids and congeners at GRP55, due to the different results obtained with different functional assays in various biological systems (786). It is possible that different biased signaling properties of these ligands, and tissue and celldependent coupling of GPR55 with different G proteins and effector systems, or with CB1 or CB2 in heteromers, all contribute to this heterogeneity of results (110,537,592).…”
Section: B Other Receptors For Endocannabinoidsmentioning
confidence: 99%
“…In particular, CB1 receptors were shown to form homodimers by using a "dimer antibody" as well as classical immunoprecipitation techniques, and were also reported to make heterodimers with D2 dopamine, A 2a adenosine, OX-1 orexin, 5-HT 2a serotonin, opioid, AT1 angiotensin II, and GPR55 receptors, the latter of which form heterodimers also with CB2 receptors (373, 509, 592, 669). Interestingly, there is also a report of the occurrence in the brain of CB1/CB2 heterodimers, the coactivation of which results in a negative crosstalk over Akt phosphorylation and neurite outgrowth (110).…”
mentioning
confidence: 99%